2018
DOI: 10.1007/s11250-018-1534-6
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of enterotoxins, toxic shock syndrome toxin-1, and biofilm formation genes in Staphylococcus aureus isolates from cows with mastitis in the Northeast of Brazil

Abstract: Staphylococcus aureus is among the microorganisms more frequently associated with subclinical bovine mastitis. S. aureus may produce several virulence factors. This study aimed at determining the frequency of virulence factors such as enterotoxins, toxic shock syndrome toxin 1, and ica adhesion genes. In addition, we assessed antimicrobial drug resistance in S. aureus isolated from clinical and subclinical cases of mastitis. A total of 88 cows with clinical or subclinical mastitis were sampled, resulting in 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
0
12
0
3
Order By: Relevance
“…Comparison of S. aureus genotypes isolated from either bovine, ovine, or caprine animals suffering from mastitis suggests the existence of specific S. aureus clonal types for each of the animal groups; the bacterium appears to have developed distinct virulence mechanisms to specifically target these three ruminant groups. These studies centered on the prevalence of individual toxins, with the aim of understanding the role of each particular toxin in the development of mastitis [12,13,[15][16][17][18][19][20][21][22][23]. Indeed, Vaughn and coworkers [13] studied the genotypes of individual S. aureus isolates, identified from cases of bovine mastitis in east Tennessee.…”
Section: Role Of Staphylococcus Aureus Toxic Proteins In Mastitismentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of S. aureus genotypes isolated from either bovine, ovine, or caprine animals suffering from mastitis suggests the existence of specific S. aureus clonal types for each of the animal groups; the bacterium appears to have developed distinct virulence mechanisms to specifically target these three ruminant groups. These studies centered on the prevalence of individual toxins, with the aim of understanding the role of each particular toxin in the development of mastitis [12,13,[15][16][17][18][19][20][21][22][23]. Indeed, Vaughn and coworkers [13] studied the genotypes of individual S. aureus isolates, identified from cases of bovine mastitis in east Tennessee.…”
Section: Role Of Staphylococcus Aureus Toxic Proteins In Mastitismentioning
confidence: 99%
“…The entB and entC1 genes, encoding the SEB and SEC proteins respectively, were the first genes amplified by PCR in dried skim milk powder; while dairy products, meat, and traditional sweets have been analyzed using multiplex PCR to detect the S. aureus 16s rRNA, as well as the sea, seb, sec, sed, and see genes [52]. Several studies have used multiplex PCR to amplify a variety of toxin genes, in combination with genes associated with biofilm formation, such as icaA and icaD [20], clumping factor (clfA), or protein A (spa) [15]; these co-amplifications helped establish the relationships between those genes, as well as furthering research into their role in staphylococcal infections. In addition, both PCR and ELISA techniques have been successfully used to investigate the presence of a variety of genes in beef and lamb meat; these genes include those corresponding to SE (sea, seb, sec, sed, and see), several SEI toxins (seg, seh, sei, sej, sel, sem, and seo), exfoliative toxins (eta and etb), and the toxic shock syndrome 1 toxin (tst) [40].…”
Section: Staphylococcus Aureus Toxin Identification Using Genomic Metmentioning
confidence: 99%
“…The biofilm formation ability of S. aureus is an important virulence factor associated with chronic IMI, which can be difficult to detect within herds (Cucarella et al., 2004; Gomes et al., 2016). On a regular basis, subclinical mastitis diagnosis is performed using the California mastitis test (CMT) and somatic cell count (SCC) (Costa et al., 2018). However, Petzer et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2004), who also observed that 22.6% of infected cows were incorrectly classified as uninfected with the SCC criteria (<200.000 cells/mL), when in fact these cows were infected with the genotypes best capable of forming biofilms. These microorganisms can remain undetected in the udder, the biofilm-forming strains may cause misdiagnosis of IMI, allowing the persistence of this pathogen in dairy herds (Costa et al., 2018; Cucarella et al., 2004). In this work, we found that 81.26% of S. aureus isolates were biofilm formers in vitro , which supports results shown by Coelho et al.…”
Section: Discussionmentioning
confidence: 99%
“…Íàèáîëåå ýôôåêòèâíûìè ïðîòèâîìèêðîáíûìè ñðåäñòâàìè ïðîòèâ èçîëÿòîâ áûëè ãåíòàìèöèí, àìîêñèöèëëèí è íîðôëîêñàöèí. Ìåíåå ýôôåê-òèâíûìè áûëè ïåíèöèëëèí, ñòðåïòîìèöèí è àìïèöèëëèí [2,3,4,8].…”
unclassified